Categorical and Dimensional Diagnoses of Dyslexia: Are They Compatible? - Cilibrasi, Luca; Tsimpli, Ianthi (Frontiers in Psychology, 2020)
Dyslexia is often assessed using categorical diagnoses, and subtypes of dyslexia are also recognised in a categorical fashion. Children may meet the criteria for dyslexia, and they may more specifically meet the criteria for a subtype of it, and thus get a diagnosis. This approach to diagnosis clashes with the actual distribution of reading performance in children (which is normal and continuous), and it has received criticism. This paper offers a conceptual framework for conciliating these two positions. In short, the proposal is to use a set of multicomponent continuous assessments of reading, rather than thresholds. The proposal is explained using original data obtained from a sample of 30 children (age 7 to 11), tested in the UK. Using an assessment based on categorical-thresholds, only 5 children in our sample qualify for extra assistance, and only 1 may get a diagnosis of dyslexia, while with the mixed system proposed, a few additional children in the grey area would receive attention. This approach would not discard previous categorical approaches such as those distinguishing between surface and phonological dyslexia, but it would rather see these subtypes of dyslexia as the instance of a lower score on the continuum obtained on a single component of the multicomponent assessment.